Pathomechanics of lumbrical and flexor digitorum profundus muscle tears in climbers: A cadaveric model - Carnicero, N.; Claramunt, A. F.; del Valle Jou, M.; Casado, A.; Rodríguez-Baeza, A. (Journal of Biomechanics, 2024)
Lumbrical muscles originate on the flexor digitorum profundus (FDP) tendons and, during fist making, they move in the same direction when FDP muscle produces maximal proximal tendon gliding. Injuries of the bipennate lumbricals have been described when a shear force acts between the origins on adjacent tendons of the FDP, as they glide in opposite directions in asymmetric hand postures. Other structures of the deep flexors complex can be affected during this injury mechanism, due to the so-called quadriga effect, which can commonly occur during sport climbing practise. Biomechanical studies are needed to better understand the pathomechanism. A cadaveric study was designed to analyse the effects of load during the fourth lumbrical muscle injury mechanism. The amount of FDP tendon gliding and metacarpophalangeal (MCP) joint flexion of the 5th finger were calculated. Ten fresh-frozen cadaveric specimens (ten non-paired forearms and hands) were used. The specimens were placed on a custom-made loading apparatus. The FDP of the 5th finger was loaded, inducing isolated flexion of the 5th finger, until rupture. The rupture occurred in all specimens, under a load of 11 kg (SD 4.94), at 9.23 mm of proximal tendon gliding (SD 3.55) and at 21.4° (SD 28.91) of MCP joint flexion. Lumbrical muscle detachment from the 4th FDP was observed, from distal to proximal, and changes in FDP tendons at the distal forearm level too. The quadriga effect can lead to injury of the bipennate lumbrical muscles and the deep flexors complex in the hand and forearm.